The Impact of Nickel Downstreaming Policy on Environmental Damage in Konawe Regency, Southeast Sulawesi - Aldi Kusuma; Dustin Ahmad Baihaqqi; Defira Alya Salsabila; Bintang Mahardika Pramanda Aji; Iradhad Taqwa Sihidi (Indonesian Journal Publisher, 2026)
This study analyzes the ecological impacts of Indonesia’s nickel downstreaming policy on biodiversity and local ecosystems in Konawe Regency, Southeast Sulawesi, using a political ecology approach. A qualitative descriptive method was employed based on literature review and secondary data from policy documents, government reports, scientific publications, and environmental agency records. The analysis examined land cover change, habitat fragmentation, degradation of aquatic ecosystems, and power relations in nickel mining governance.The findings indicate that the expansion of downstream nickel industries has accelerated forest conversion, fragmented terrestrial habitats, increased river sedimentation, and reduced aquatic habitat quality, thereby threatening local biodiversity sustainability. These environmental pressures are closely linked to governance dynamics in which economic growth and state interests dominate decision-making, while environmental protection and conservation measures receive limited attention.From a political ecology perspective, the downstreaming policy reproduces unequal power relations that marginalize ecological considerations at the local level. The study concludes that the effectiveness of downstreaming should not be assessed solely through economic indicators but must incorporate ecological sustainability and biodiversity safeguards. Policy reform is required to integrate environmental carrying capacity, strengthen local monitoring mechanisms, and ensure more inclusive and balanced governance of resource extraction